High diffusion barrier and piezoelectric nanocomposites based on polyvinylidene fluoride‐trifluoroethylene copolymer and hydrophobized clay. Issue 24 (12th September 2017) - Dalle Vacche, Sara; Oliveira, Fabiane; Sereda, Olha; Neels, Antonia; Dommann, Alex; Damjanovic, Dragan; Leterrier, Yves
ABSTRACT: Nanocomposites based on polyvinylidene fluoride–trifluoroethylene copolymer and up to 4 vol % of hydrophobized clay nanoparticles are investigated. The structure, piezoelectric properties, and oxygen permeability of solvent cast films are analyzed before and after annealing above the Curie temperature of the polymer. Exfoliation of the clay takes place at concentrations up to 1 vol %, beyond which it rapidly drops and is absent at a concentration of 4 vol %. The presence of clay does not change the crystallinity of the polymer, but leads to a threefold decrease of the oxygen permeability at a concentration of 0.5 vol %. Annealing at 130 °C increases the crystallinity, the proportion of β phase up to 94%, and the piezoelectric coefficient by 20–40% at clay fractions below 1 vol %. Annealing also leads to a remarkable 3‐ to 10‐fold decrease of O2 permeability and to intriguing changes of the activation energy for O2 transport, which decreases from 56 kJ/mol for the as‐cast polymer to below 10 kJ/mol for the polymer and exfoliated composite. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2017, 55, 1828–1836 Abstract : The addition of hydrophobized clay particles to a piezoelectric fluorinated polymer and to the annealing of the resulting exfoliated composites considerably decreases the gas permeability of the material and the associated activation energy. Moreover, the piezoelectric coefficient d 33 of the exfoliated and annealed composites is 20–40% higher than that of the as‐cast polymer. Such a remarkable combination of gas barrier and piezoelectricity is interesting for creating self‐sensing liners for high‐pressure gas storage vessels.